Influence of impeller submergence depth on power consumption in stirred tank (Chemical Engineering Research Bulletin, 2011)
Impeller submergence governs the performance of mixing tanks employed in chemical and biochemical operation. Present work experimentally investigates the effect of impeller submergence depths on power consumption when arrow head impeller has been used in the process. Arrowhead impeller performs better than the conventional Rushton impeller. It has been found that at higher range of impeller submergence, mixing tanks consume less power. Optimal range of submergence depth is 0.8 to 0.9 times the impeller diameter.Key words: arrowhead impeller; power consumption; rotational speed; stirred tanks; submergence depthDOI: http://dx.doi.org/10.3329/cerb.v15i1.7098 Chemical Engineering Research Bulletin 15 (2011) 45-47